Preface - Kopińska, Violetta (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
Issue 42 of the Przegląd Badań Edukacyjnych [Educational Studies Review] is the latest entry in the Kobiety w Edukacji/Kobiety o Edukacji [Women in Education/Women about Education] series.The current issue is centred on women/girls’ citizenship activity or gender of citizenship activity.